Neutropenic sepsis and septic shock in ICU patients: A single-center experience over the last decade - Florian Guillotin; Laetitia Aubert; Soraya Benguerfi; Reyes Munoz Calahorro; Alice Vennier; David Boutoille; Thomas Gastinne; Jean Reignier; Jean-Baptiste Lascarrou; Matilde Karakachoff; Emmanuel Canet (PLoS ONE, 2025)
Purpose Sepsis and septic shock in patients with neutropenia are associated with high mortality. We investigated the features and outcome predictors of neutropenic sepsis in the last decade. Methods Consecutive patients who were admitted to the intensive care unit (ICU) of a French university-affiliated hospital in 2012–2022, met criteria for sepsis or septic shock, and had neutropenia were included retrospectively. Patient features were collected and compared for 2012–2017 and 2018–2022. Factors associated with hospital mortality were sought by univariate and multivariate analyses. Results Of the 185 patients, 85 were admitted in 2012–2017 and 100 in 2018–2022. The more recent group was older and had a heavier comorbidity burden but had a hospital mortality rate of 40.0% compared to 49.4% in the early group (p = 0.24). The most common source infections were pulmonary (24.8%) and hepatobiliary or gastrointestinal (23.8%). Gram-negative bacilli predominated. Predictors of in-hospital mortality were older age (odds ratio [OR], 1.04; 1.01–1.07; P = 0.005) and worse SOFA score (OR, 1.22; 1.05–1.42; P = 0.009). Aminoglycoside therapy predicted lower in-hospital mortality regardless of infection site and renal function (OR, 0.30; 0.14–0.63; P = 0.002). Early source-control interventions were not significantly associated with hospital mortality. Conclusion Intensivists are admitting patients with neutropenic sepsis who are older and have more comorbidities than was the case in earlier years. Despite this change, there is a non-statistically significant trend of declining mortality. Our findings support the initiation at ICU admission of combination antibiotic therapy including an aminoglycoside.